(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The article provides information on the study of new F1 eggplant hybrids. In the research work F1 Zamin, st., F1 L-29xGel, F1 SsxSur.g, F1 GelxL-29, F1 MkxSur.g, F1 MkxL-29 hybrids and their parent forms were obtained. F1 MkxL-29 hybrids were classified as hybrids with a high heterosis effect in terms of total and early yield